Sharia Expression in Contemporary Indonesia: An Expansion from Politics to Economics - M Zainal Anwar (Universitas Islam Negeri Mataram, 2018)
This study aims to describe the expression of sharia in contemporary Indonesia especially in the post reform era. In the beginning of reform, sharia appeared as the political actualization indicated with the demand for returning the seven words of the Jakarta Charter to the local government bylaws. Recently, sharia extends its coverage to economic fields, such as accommodation in industry with the emergence of sharia-labeled hotels, halal tourism and the like. This article departs from an argument stating that the extension of the meaning of sharia is inseparable from the interest of actors utilizing its label or brand to show political identity and business interests. This article describes this shift and analyzes the factors that affect this shifting from politics to economics. Drawing from the theoretical perspective of the contemporary sharia, stating that sharia contains a broad spectrum applied to many levels and aspects, this article argues that that sharia no longer has a single normative definition but has encountered meaning development corresponding to the social and historical challenges. This article also shows that sharia expansion into economic fields is now ongoing process in contemporary Indonesia.